XI-th Workshop and Awards for young researchers in the field of statistical physics and condensed matter theory (Condensed Matter Physics, 2010)
The XI-th Anniversary Workshop will be held in Lviv at the Institute for Condensed Matter Physics on June 1–3, 2011.